Perfil bioquímico do extrato de Croton argyrophyllus e seus efeitos antioxidantes em ratas submetidas ao exercício físico resistido de alta intensidade - Lima, Douglas Bonfim (2014)
Exercise is an important tool for maintaining health and preventing several diseases like diabetes, hypertension and obesity. Additional treatments have been implemented for these patients and physical exercise stands out in this context. However, acute weathered exercise high intensity favors the production of free radicals, which can cause oxidative stress that leads to injury in the body. Have tried different ways to reduce this process, for example, through the use of natural products such as extracts of plants to alleviate the effects of free radicals due to the presence of antioxidants in that. This study aimed to investigate the phytochemical profile of the hydroethanolic extract of C. argyrophyllus and evaluate its effect on free radicals and in vitro against oxidative stress induced by acute weathered exercise high intensity in female rats. In the present study, the phytochemical profile of the hydroethanolic extract of stem bark of C. argyrophyllus was investigated by colorimetric reactions or precipitation, while the content of total phenols was quantified using the Folin-Ciocalteu method. The extract also was tested in vitro on the model radical DPPH and to study its effect on oxidative stress, female Wistar rats (200-250 g) were divided into 4 groups: 1) Group sedentary vehicle (TW-EE, n = 7) - composed of sedentary animals treated with vehicle (Tween 80, orally), 2) Group trained vehicle (TW-EX n = 6) - consists of animals treated with vehicle (Tween 80) and subjected to protocol weathered training; 3) Group sedentary extract (EHE-EE, n = 6) - composed of sedentary animals treated with extract of C. argyrophyllus (200 mg/kg); 4) Group trained extract (EHE-EX, n = 7) composed of trained animals with weathered exercise and treated with EHE of the C. argyrophyllus (200 mg/kg). The results were presented as mean ± standard error of the mean, using p <0.05. All analyzes were performed in triplicate. After evaluating the normality of the data through the Shapiro-Wilk test, they were evaluated using the Student t test or one-way analysis of variance followed by post hoc Bonferroni. Graph Pad Prism 5.0 software was used. The animals received the extract or vehicle 1h before performing the exercise, being euthanized 1h after training. The substances found in the extract were steroids, flavanones, flavananóis, flavones, flavonoids, tannins, xanthones and terpenes. Due to the low phenolic content (64.68 ± 9.06 mg-eq AG/g) in the extract, was observed percentage inhibition of DPPH next to 40% with low AAI (0.12). Acute administration of the extract reduced, the trained group, CK concentrations in plasma (54.13%) and muscle (46.35%); LDH in the plasma (30.53%); and MDA (65.51%) compared to those receiving the vehicle Tween 80. The extract also reduced in the sedentary group, plasma LDH (47.14%) and muscle (65.43%). Thus, the results show that the hydroethanolic extract of C. argyrophyllus has several antioxidant compounds. Although it has not shown good effect in the model of radical DPPH , was observed significant protection against oxidative stress based on markers of tissue injury CK, LDH and MDA.